Analysis of poisoning with OTC drugs for suicidal purposes among children and adolescents in Poland in the period 2012 - 2023: Paracetamol as the most frequently used substance in intentional poisonings - Kubicka, Maria; Polańska, Paulina; Gruszka, Marta; Zakrocka, Martyna (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Drug poisoning among children and adolescents is an increasing public health issue worldwide and in Poland. Intentional poisonings, especially suicide attempts, are on the rise, often involving over-the-counter (OTC) medications, with paracetamol being the most commonly used substance. This paper aims to analyze the prevalence, characteristics, and implications of drug poisonings in youth, focusing on social and mental health factors, particularly during the COVID-19 pandemic. Materials and Methods: The study is based on retrospective data collected from Polish cities published between 2014 and 2023, examining hospital admissions, demographic trends, and poisoning agents. Results: The study reveals a significant increase in suicide attempts, especially during the COVID-19 pandemic. Paracetamol poisoning remains the leading cause of intentional overdoses, with severe cases potentially resulting in acute liver failure or death if untreated. Girls account for a disproportionate number of cases, and many adolescents who attempt suicide lack prior psychiatric diagnoses. Seasonal trends and shifts in age demographics suggest changing patterns in poisoning incidents. Conclusions: The findings emphasize the need for improved mental health education, early intervention, and caregiver awareness. Strengthening psychological support and implementing stricter regulation of OTC drugs are crucial to addressing the root causes of youth suicide attempts. Proactive measures, such as teaching problem-solving skills and expanding access to mental health services, are essential to mitigating this growing public health challenge.